Evolução metamórfica e termobarometria das rochas metamáficas/metabásicas da região de Pontalina - GO - Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; Simões, Luiz Sérgio Amarante [UNESP] (My University, 2011)
At the Pontalina region, the Magmatic Arc of Goiás is constituted by orthogneisses, metasediments, metaultramafics and metamafic/metabasics, geochemically related to island arcs. Mineral assemblages related to metamorphic peak observed in the study area are typically of the amphibolite facies and were generated before or during the initial stage of the development of the main foliation (S n). Thermobarometric data show the P and T conditions for the amphibole + plagioclase and plagioclase + garnet + amphibole assemblages in the metamafic/metabasic rocks correspond to amphibolite facies (medium to upper grade), and plot in the kyanite stability field. The results indicate that the metamorphic peak (M1) in the amphibolite facies (medium up to upper grade) reached temperatures slightly higher than 700°C, not exceeding 775°C, under conditions of medium pressure (∼10 kbar). Thermobarometric and petrographic data, related to the metamorphism, indicate a clockwise P-T path for the surrounding rocks.
Metamorphic and thermobarometry evolution of the metamafics/metabasics rocks in Pontalina region, state of Goiás
Keywords: Metamafics/Metabasics rocks; Mineral chemistry; Thermobarometry